Swarm intelligence methods for statistical regression - Mohanty, Soumya D. (CRC Press, Taylor & Francis Group, 2019)
A core task in Big Data analytics is the fitting of flexible, high-dimensional, models to noisy data in order to capture meaningful patterns. This book will describe methods from the field of computational swarm intelligence (SI) and how they can be used to solve optimization problems encountered in Big Data analytics. It will consider some generic data analysis problems, and how they may be addressed using SI methods.